SUPPLY CHAIN TRANSPARENCY ANALYSIS OF PATCHOULI OIL INDUSTRY IN ACEH FROM SEED TO INTERNATIONAL MARKET - Ulya, Zaudhatul; Haikal, Muhammad; Lufika, Raihan Dara; Vonna, Adinda Gusti; Mandira, Ade Surya; Melinda, Zikrina (Departemen Teknik Industri, Fakultas Teknik, Universitas Diponegoro, 2026)
Patchouli is one of the most valuable export commodities in Aceh. Patchouli oil must meet several qualifications to obtain export eligibility certification, particularly in terms of its environmental impact, where an in-depth analysis of supply chain transparency is necessary, spanning from seed procurement to distribution and entry into the international market. Despite the large potential for patchouli oil production, industries in Aceh face critical challenges related to supply chain transparency and traceability, which undermine efforts to meet sustainability standards and global market requirements. This study analyzes the transparency of the patchouli oil procurement at the PP NILAS Cooperative and the distribution process through PT Ugreen to the buyer, two key institutions in the local value chain. This study use an exploratory case study approach, combining field observation, purposeful sampling, and semi-structured interviews with key stakeholders, including farmers, distillers, intermediaries, exporters, cooperatives, and Non-Governmental Organization (NGO)s. The study found traceability gaps across several elements of the supply chain, limited documentation practices among smallholders, and challenges in aligning local operations with global certification demands. The study highlights the need for supply chain digitalization, inclusive training, and multi-stakeholder collaboration to strengthen supply chain transparency and support sustainable export growth for the Aceh patchouli industry.